2008
DOI: 10.1089/lap.2007.0156
|View full text |Cite
|
Sign up to set email alerts
|

Use of Video Capsule Endoscopy in the Setting of Recurrent Subacute Small-Bowel Obstruction

Abstract: "Use of video capsule endoscopy in the setting of recurrent subacute small-bowel obstruction." Journal of Laparoendoscopic & Advanced Surgical Techniques.18,5. 713-716. (2008 AbstractHypothesis: Video capsule endoscopy (VCE) can be used to diagnose subacute intestinal obstruction in patients with otherwise negative imaging studies. Patients and Methods: Nine patients with symptoms consistent with intermittent small-bowel obstruction who received a VCE and ultimately required surgical intervention. Results: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Although several studies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and two metaanalyses [47,48] have addressed this issue, there are no guidelines yet concerning the preparation before capsule endoscopy. Our survey shows that the large majority of patients (80%) take laxatives before the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and two metaanalyses [47,48] have addressed this issue, there are no guidelines yet concerning the preparation before capsule endoscopy. Our survey shows that the large majority of patients (80%) take laxatives before the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs overall in about 1-2.5% [27,32] of patients undergoing this examination, but this complication can reach 20-25% in some selected groups of patients (i.e. patients with small bowel obstruction or small bowel tumors) [33][34][35]. To ascertain the true impact of capsule retention in everyday clinical practice these data should be collected in a large multicenter setting and, possibly, covering a long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some authors have reported that NSAID-induced stricture was the major cause of capsule retention [6,7] . Recently, Mason et al [8] have reported that intestinal mass or radiation enteritis are the main causes of subacute small bowel obstruction. The different causes of stricture may be associated with the indications of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the premise that the retained capsule leads to surgical treatment of the diseased bowel and removal of capsule to alleviate the symptoms, CE has been used in the setting of recurrent subacute small bowel obstruction to find the cause of symptoms and localise the disease [414,415]. Ultimately, surgical intervention is required in most cases of capsule retention due to underlying pathology requiring surgical resection such as small bowel tumours [359,372,373], and also to deal with complications such as small bowel obstruction or perforation.…”
Section: Managing Capsule Retentionmentioning
confidence: 99%